Mapping art collecting in Europe, 1860-1940 Eastern and Western sociocultural perspective - International Conference "Collection, Modernism and Social Identity - Art Collecting in Europe between 1880-1940"; Woźniak, Milena; Collection, Modernism and Social Identity. Art Collecting in Europe Between 1880–1940 (Fokus, 2023)
The essays cover a broad scope of issues relating to individual identity strategies and art collecting in the late modern era, encompassing the history of museums, exhibition policy, art market history, history of taste shaping and provenance research. They create a comparative pan-European perspective of the collecting phenomenon in its various facets. The detailed analysis of the individual cases shows how collecting mirrored the social problems of the late modern era. The book adresses issues such as the socio-cultural role of ethnic minorities, the question of women's emancipation, social exclusion versus inclusion, colonialism or the politicisation of museums. When analysed in the context of private collections, these issues gain clarity and simultaneously demonstrate the complexity of cultural processes, which are still not sufficiently recognised